2023
DOI: 10.1002/ijgo.14953
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of topical imiquimod in high‐grade cervical intraepithelial neoplasia: A systematic review and meta‐analysis

Abstract: ObjectiveA major side effect of cervical excision for high‐grade cervical intraepithelial neoplasia (CIN) is premature birth. A non‐invasive treatment for reproductive age women is warranted. The aim of the present study was to determine the efficacy of topical imiquimod in the treatment of high‐grade CIN, defined as a regression to ≤CIN 1, and to determine the clearance rate of high‐risk human papillomavirus (hr‐HPV), compared with surgical treatment and placebo.MethodsDatabases were searched for articles fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Comparing the efficacy of imiquimod to standard large loop excision a recent meta-analysis confirms the superiority of surgical excision in HSIL (OR: 14.81, 95% CI 6.59-33.27), 89 with a response rate of 37%-63% in imiquimod treated versus 92.3%-94% for large loop excision. Furthermore, the authors reported an HR-HPV clearance rate of 53.4% after imiquimod treatment and 66% after surgical excision (95% CI 0.62-23.77).…”
Section: Cervical Intraepithelial Neoplasiamentioning
confidence: 90%
See 3 more Smart Citations
“…Comparing the efficacy of imiquimod to standard large loop excision a recent meta-analysis confirms the superiority of surgical excision in HSIL (OR: 14.81, 95% CI 6.59-33.27), 89 with a response rate of 37%-63% in imiquimod treated versus 92.3%-94% for large loop excision. Furthermore, the authors reported an HR-HPV clearance rate of 53.4% after imiquimod treatment and 66% after surgical excision (95% CI 0.62-23.77).…”
Section: Cervical Intraepithelial Neoplasiamentioning
confidence: 90%
“…Imiquimod dose was 6.25 mg for vaginal suppository, 70 while those using imiquimod cream used either a half-sachet dose (6.25 mg) 74 up to a full sachet of Imiquimod 5% cream (12.5 mg). 72,89 Only one study 69 Several randomized controlled trials evaluated the role of imiquimod cream for CIN treatment: the first, compared a vaginal 6.25 mg imiquimod suppository for 14 weeks to a placebo in 69 CIN 2-3 untreated patients. 70 Histological complete remission was reported in 47% in the imiquimod arm and 14% in the placebo group (p-value = 0.008), while overall regression (defined as histologic regression to CIN1 or less at 20 weeks) in 73% versus 39%…”
Section: Cervical Intraepithelial Neoplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, alternative conservative methods for SIL treatment are constantly being evaluated, and imiquimod (IMQ), a synthetic tolllike receptor 7 (TLR7) agonist, has generated attention for its potential to stimulate local antitumor and antiviral immune responses. Although studies have shown that IMQ is effective for treating vulvar intraepithelial neoplasia (VIN) [3], vulvar Paget disease [4], vaginal intraepithelial neoplasia (VaIN) [5], and CIN when compared to placebo or no intervention [6], its exact mechanism of action remains unclear [7].…”
Section: Introductionmentioning
confidence: 99%